2019
DOI: 10.1097/ajp.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

School Absence Associated With Childhood Pain in the United States

Abstract: Objective: To estimate the national burden of school absenteeism associated with pain among 6-17 year old children in the United States. Methods: Data were analyzed from a large, nationally representative sample from the 2012 National Health Interview Survey. Associations between pain and school absence were analyzed using multivariate negative binomial models controlling for sociodemographic and clinical characteristics. Results: The sample contained 8641 participants, of whom 30.3% reported pain over the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…CYP with chronic pain have a higher rate of absenteeism than other chronic health conditions. 90 The most common clinical manifestations of anxiety among CYP with chronic pain include school phobia, separation anxiety and social anxiety. 91 physical symptoms at school and negative peer evaluation.…”
Section: Mental Health and Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP with chronic pain have a higher rate of absenteeism than other chronic health conditions. 90 The most common clinical manifestations of anxiety among CYP with chronic pain include school phobia, separation anxiety and social anxiety. 91 physical symptoms at school and negative peer evaluation.…”
Section: Mental Health and Transitionmentioning
confidence: 99%
“…91 physical symptoms at school and negative peer evaluation. 90 Unfortunately, comprehensively measuring the impact of the chronic pain and chronic disease on school anxiety has not been established. Understanding the duality of chronic pain and disease burden on school related anxiety is incredibly important in JIA as pain often persists after treatment of the inflammatory phase.…”
Section: Mental Health and Transitionmentioning
confidence: 99%
“…8 As in a recent study, addressing functional limitations due to all types of pediatric chronic pain, we examined functional limitations primarily using a continuous measure of school absenteeism (number of missed school days due to illness or injury over the past 12 months). 12 To further characterize the association between headache and functional limitations, we used a question from the Strength and Difficulties Questionnaire, which asked whether the child had difficulties with emotions, concentration, behaviors, or getting along with others. 13 Responses to the latter question were reported on an ordinal scale (no difficulties, minor difficulties, definite difficulties, and severe difficulties).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of chronic pain in this age group has a negative impact on quality of life, damaging the social, recreational, and academic domains, also being a major cause of absenteeism in children and adolescents. Chronic pain is associated with increased school abstention (Groenewald et al, 2019), and, as shown by prospective cohort studies, chronic pain in adolescents was associated with lower education levels in adulthood, worse career positioning, and other social impacts such as early parenthood and a worse quality in affective relationships (Murray et al, 2020).…”
Section: Introductionmentioning
confidence: 93%